(untitled) (Argos, 2025)
Reading, appropriation and re-signification of former literary and philosophical tradition was a common practice, conservative and innovative at the same time, at Late Antiquity. This double practice consisted of the claim to auctoritas of ancient texts, and by the other hand, of its relocation on contemporary times, a ruling aspect at defining cultural identity. At Macrobius’ works, doctrina rises from verecundia and diligentia, and these concepts take at this author, if not a different perspective, at least another dimension in its relationship with Classical culture.